High Protein Complementary Feeding Education with Cooking Demonstration for Stunting Prevention Among Pregnant Women in Gunungtugel Village, Wonosobo - Wibowo, Shaviera; Nurhidayati, Siti; Ratriyanto, Adi; Shauma, Clara; Mawarni, Dini; Ramadha, Intan; Dydanti, Kanaya; Prasetyo, Medina; Ar Roffi, Muhammad; Alfareza, Muhammad; Siota, Rizky; Saputri, Shava (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2025)
Stunting remains a major public health problem in Indonesia, primarily associated with not optimal feeding practices during the first 1,000 days of life. One important preventive effort is preparing mothers during pregnancy to make sure they have adequate knowledge and skills to prepare nutritious complementary feeding that provides sufficient protein to support child growth. This community service aim to provide education on high protein complementary feeding combined with cooking demonstrations as a strategy for stunting prevention in Gunungtugel Village, Wonosobo, Indonesia. The intervention was implemented through a pregnant women class consisting of education sessions using leaflet based materials that addressed the principles of complementary feeding, the importance of adequate protein intake, identification of locally available protein sources, age appropriate food texture, and hygienic food preparation practices, followed by a cooking demonstration of high protein complementary feeding. Data collection was carried out through pre and post interviews, participatory observation, and field documentation. The results indicated an improvement in mother’s understanding of high-protein complementary feeding, their ability to identify appropriate protein sources, and increased confidence in preparing complementary foods independently. Participants also demonstrated a better understanding of the role of protein in supporting child growth and preventing stunting. These findings suggest that high protein complementary feeding education combined with cooking demonstrations for pregnant women can be an effective community empowerment approach to improve maternal in implementing appropriate complementary feeding practices and supporting stunting prevention efforts.